THE INFLUENCE OF ACTIVITY PLANNING, FUND WITHDRAWAL PLANNING AND ACCURACY ON BUDGET REALIZATION USING FORECASTING IN THE NON VERTICAL SPECIFIC WORKING UNITS OF WATER UTILIZATION NETWORK IMPLEMENTATION OF MESUJI SEKAMPUNG IN 2014-2016 - Hairudin Hairudin; Adhi Nurhartanto; Hasbullah Hasbullah (JURNAL MANAJEMEN DAN BISNIS, 2020)
The purpose of this research is to examine and determine the effect of activity planning, fund withdrawals and accuracy of budget realization in certain non-vertical work units in the implementation of mesuji water use networks in the 2014-2016 period. This research uses descriptive and quantitative methods from the results of financial statements for 3 years with 1 company. By using the classic assumption test, multiple linear regression analysis, and hypothesis testing. The results of multiple regression analysis with Y = -22,513 + 1,741 (X1) + 0,172 (X2) + 0,071 (X3) + e indicate that the variable planning activities and withdrawing funds together have a significant effect on budget realization.